Analisis pengaruh faktor fundamental terhadap harga saham perbankan - Natania Naftali; Ika Nur Azmi; Haryono Haryono (Akuntansi dan Teknologi Informasi, 2024)
This research examines the influence of fundamental factors (ROE, NPM, and EPS) on stock prices. This research is a type of associative quantitative research category through purposive sampling in obtaining a sample of 39 companies. All banks listed on the Indonesian Stock Exchange (IDX) in the 2019-2022 period are the target population of the research. This study collected archival data from official IDX website. The data is analysed using multiple linear regression with the help of the SPSS 26.0 Data Processing Software Application. The results showed that ROE and NPM have no significant effect on stock prices partially. Meanwhile, EPS has a significant effect on banking stock prices. A higher increase in EPS will have a significant impact on the raising of firm value in the capital market. For investors, EPS can be a major consideration in determining investment decisions. For banking companies, it is important to pay attention and improve the company's performance, especially related to EPS which has a significant influence on the increase in stock prices.